Towards a Taxonomy of Microservices Architectures - Garriga, Martin (Software Engineering and Formal Methods, 2018)
The microservices architectural style is gaining more and more momentum for the development of applications as suites of small, autonomous, and conversational services, which are then easy to understand, deploy and scale. However, the proliferation of approaches leveraging microservices calls for a systematic way of analyzing and assessing them as a completely new ecosystem: the first cloud-native architectural style. This paper defines a preliminary analysis framework in the form of a taxonomy of concepts, encompassing the whole microservices lifecycle, as well as organizational aspects. This framework is necessary to enable effective exploration, understanding, assessing, comparing, and selecting microservice-based models, languages, techniques, platforms, and tools. Then, we analyze state of the art approaches related to microservices using this taxonomy to provide a holistic perspective of available solutions.